Second-order torsion effects in concrete buildings - Rodrigo Bezerra Andrade; Petrus Gorgônio Bulhões da Nóbrega (Revista IBRACON de Estruturas e Materiais, 2020)
ABSTRACT: The internal forces due to torsion in global analysis of buildings, and its second-order effects, usually are not properly considered in structural design or even in design code’s prescriptions. Although the γZ coefficient, which is used to the evaluation of global second-order effects, has a wide, useful and consolidated application, it is true that specific torsional aspects are not well considered by it. This paper discusses the little-known γθ coefficient, an analogous proposition to the γZ coefficient, but focused specifically on the consideration of torsional effects. After the discussion on the concepts and the design methodology, several buildings are evaluated and their displacements and the coefficients γZ and γθ are calculated. Comparing these parameters, and also the results obtained by the P–Δ method, it is demonstrated the importance and the reliability of the γθ coefficient.